PENINGKATAN KINERJA UKM MELALUI IMPROVEMENT PROCESS DI KABUPATEN PURBALINGGA - IVAN SUTRISNO; RAHAB .; JARYONO . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
Improving of SMEs performance need good management system. The purpose of this researchis analyze the factors influencing the performance of SMEs and to determine whether thevariables of innovation, environmental hostility and firm size affect to improvement processs.A survey was conducted in Purbalingga regency by purposive sampling technique. Thesamples that are used to data analysing are 110 small medium enterprises. Partial LeastSquares method was used to examine 6 (six) research hypotheses. Research instrumensvalidity was measured by convergent validity and discriminant validity. Instrument reliabilitywas measured by cronbach’s alpha and composite reliability. The result shows that innovationand firm size positively effect to improvement process. Improvement process has a positiveeffect on firm’s growth.Keyword : Process Improvement, Small Medium Enterprises (SMEs), Performance, Inovation